2009
DOI: 10.1016/j.nbd.2009.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Soluble fibrillar oligomer levels are elevated in Alzheimer's disease brain and correlate with cognitive dysfunction

Abstract: Recent evidence has suggested a role for soluble oligomeric Aβ species in the pathology of Alzheime's disease (AD). Fibrillar plaque deposits are present in non-demented individuals and levels of soluble Aβ correlate better with cognitive dysfunction in AD and transgenic mouse models. We have previously reported that there are at least two conformationally distinct types of Aβ oligomers: prefibrillar oligomers that are kinetic intermediates in fibril assembly reactions and are specifically recognized by A11 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
245
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(267 citation statements)
references
References 38 publications
15
245
0
2
Order By: Relevance
“…In this case, a sharp point is also drawn out from the target membrane, as is observed with short β 2 m amyloid fibrils, but instead of destroying the liposome, the destabilized, extruded membrane region is fused to the viral membrane. The cryoelectron tomography images of β 2 m fibril-membrane interactions presented here suggest that the cellular dysfunction associated with these and other fibrils or fibril-like assemblies (16)(17)(18)(19)(20)(21)27) involves direct bilayer disruption. This membrane damage might arise by direct interaction with the fibril ends and/ or by the creation of new, toxic species by reaction of the fibril ends with the lipids.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this case, a sharp point is also drawn out from the target membrane, as is observed with short β 2 m amyloid fibrils, but instead of destroying the liposome, the destabilized, extruded membrane region is fused to the viral membrane. The cryoelectron tomography images of β 2 m fibril-membrane interactions presented here suggest that the cellular dysfunction associated with these and other fibrils or fibril-like assemblies (16)(17)(18)(19)(20)(21)27) involves direct bilayer disruption. This membrane damage might arise by direct interaction with the fibril ends and/ or by the creation of new, toxic species by reaction of the fibril ends with the lipids.…”
Section: Discussionmentioning
confidence: 77%
“…In other cases, toxicity may reside with the amyloid fibrils themselves. Evidence that toxicity correlates with fibrillar assemblies has been reported for yeast and mammalian prion proteins (16,17), human lysozyme (18), Huntingtin exon 1, α-synuclein (19), and Amyloid-β (Aβ) (20,21). Furthermore, Aβ plaques have been shown to form rapidly in vivo and to precede neuropathological changes in a mouse model (22).…”
mentioning
confidence: 99%
“…Soluble oA␤ assemblies are neurotoxic in vitro and in vivo (61), and both soluble A␤ and oA␤ correlate with disease progression in AD patients (62)(63)(64)(65). We previously demonstrated that soluble levels of total A␤42 and oA␤ were increased in E4FAD transgenic mice compared with E2FAD and E3FAD, although the levels of apoE were comparable, suggesting a functional difference between the isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that this toxicity may be linked to the aggregation state of the peptide, implicating oligomers, rather than insoluble fibrils, as the primary toxic species [5,6]. While both are found in the brains of postmortem AD patients, soluble A␤ oligomers are better correlated with disease severity than are the classic amyloid plaques containing insoluble A␤ fibrillar deposits [7][8][9]. Furthermore, oligomers are found both extracellularly and intracellularly, and are capable of moving between the interior of the cell and the extracellular space [10,11].…”
Section: Introductionmentioning
confidence: 99%